The birth of the Grand Old Party : the Republicans' first generation - Engs, Robert Francis; Miller, Randall M. (University of Pennsylvania Press, 2002)
This collection of six original essays by some of America's most distinguished historians of the Civil War era examines the origins and evolution of the Republican party over the course of its first generation.